Hypothalamic-Pituitary Axis Dysfunction after Whole Brain Radiotherapy - A Cohort Study - Gebauer, Judith; Mehta, Preena; Fahlbusch, Fabian; Schmid, Sebastian M.; Rades, Dirk; Janssen, Stefan (Anticancer Research, 2020)
BACKGROUND/AIM: Hypothalamic-pituitary (HT-P) dysfunction is one of the most common endocrine late effects following cranial radiotherapy. However, there are currently no specific data describing this complication in adult-onset cancer patients after whole brain radiotherapy (WBRT). The present cohort study aims to establish the prevalence of HT-P axis dysfunction in this group of patients. PATIENTS AND METHODS: Twenty-six cancer patients previously treated with WBRT (median follow-up=20.5 months) received standardized endocrine check-up focusing on HT-P function. RESULTS: In 50% of the patients, impaired hypothalamic-pituitary function was detected during follow-up. While functional loss of a single hormonal axis was evident in 34.6% of patients, 7.7% showed an impairment of multiple endocrine axes, and one patient developed adrenocorticotropic hormone deficiency. Hypothalamic-pituitary dysfunction did not directly correlate with the applied WBRT total doses. CONCLUSION: In our cohort, hypothalamic-pituitary dysfunction appeared to be common after WBRT and was diagnosed as early as 6 months following radiation. This finding highlights the need for routine endocrine follow-up even in patients with limited life expectancy.
CRIS-Team Scopus Importer:2020-10-16
Keywords: cancer survivor; endocrine late effects; hypothalamic-pituitary dysfunction; Whole brain radiotherapy